Malaysian society and health: issues and challenges in the 21st century - Wong, Y.L.; Mohd Amin, J. (Faculty of Medicine, University of Malaya, 2005)
Malaysia, like many aspiring developing countries, is undergoing a health transition that has seen the concomitant decrease in communicable disease and increase in chronic disease due to urbanization, modernization and ageing population. Health in the Malaysian society will thus increasingly focus on emerging problems that are both chronic and infectious in nature, such as, heart disease, diabetes, cancer, mental health, hepatitis and HIV/AIDS. Re-emerging diseases previously well-controlled, such as, tuberculosis for instance is another addition to these immediate health issues facing Malaysian society today. Despite the tremendous health gains and above average health status that Malaysians now enjoy, we are compelled to take stock of these urgent issues as well as to anticipate and handle serious challenges to our health in the 21st century. In this paper, we review the changing trends and discuss related challenges in disease pattern, environmental health, demographic impacts on health, migration influxes and health, effects of globalization on health, mental and wellness as well as fundamental access and equality in health care. Being proactive, resilient and innovative, Malaysian society would forge ahead towards our Vision for Health in this new era.